An mTOR siRNA‐Loaded Spermidine/DNA Tetrahedron Nanoplatform with a Synergistic Anti‐Inflammatory Effect on Acute Lung Injury (Adv. Healthcare Mater. 11/2022). Issue 11 (8th June 2022) - Huang, Chaowang; You, Qianyi; Xu, Jing; Wu, Di; Chen, Huaping; Guo, Yuhang; Xu, Jiancheng; Hu, Mingdong; Qian, Hang
Abstract : Anti‐Inflammatory Therapy In article number 2200008 by Mingdong Hu, Hang Qian, and co‐workers, a dual therapy DNA nanoplatform consisting of spermidine and mTOR siRNA is constructed and a synergistic anti‐inflammatory effect is demonstrated in vitro and in an acute lung injury mouse model.